Lama Rawat Inap Penderita Diare Akut Pada Anak Usia Di Bawah Lima Tahun Dan Faktor Yang Berpengaruh Di Badan Rumah Sakit Umum Tabanan Tahun 2011 - Widiantari, Gusti Ayu Dewi (Community Health)
The purpose of this study was to determine the average length of stay (ALOS) of acute diarrhea among children under five years old as well as identify factors that influence it. This study uses a retrospective cohort design, where 147 acute diarrhea patients under five years old in BRSU Tabanan during January-June 2011 was defined as the cohort members and 101 out of them was selected randomly as the study samples. Secondary data was collected by reviewing medical records of a sample file. Then analyzed using  survival analysis with the Life Table method, Kaplan-Meier and Cox regression. The study results indicate that the ALOS of acute diarrhea among children under five years old was 103 (CI 95%: 94.5-112.1) hours. The ALOS among infant and patients with severe dehydration were108.2(CI 95%: 95.5-120.1) and 157.2(CI(95%:132.4-181.9) hours respectively. Infant and severe dehidration significant effect on the length of stay of acute diarrhea in children under five years old with HR = 2.02(95%CI:1.5-3.9) and 12.2(95% CI: 5.1-29.2) respectively. The ALOS of acute diarrhea  in children under five years old at Tabanan BRSU was 103 hours, it was exceed WOH standards are set for four days. Severe dehidration and age under 12 years old effect on the length of stay. It is advisable for management to improve the quality of hospital inpatient services to conform to standards established by WHO